Impact of Network Learning (Online) on The Social Interaction Of Children Aged 5-6 Years - hasibuan, santi fahrima; Sariah, Sariah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research is motivated by a phenomenon that occurred in Indonesia in 2019, namely the spread of the Covid-19 virus. So the government created distance or online learning. With this online learning, there are several children whose development of social interactions is hampered. because during the online learning process there are many obstacles that make children inactive in learning. The research method used is descriptive qualitative research. The data collection technique in this research is observation. Documentation. and Interviews and data analysis techniques in this research using data reduction. data display, and data verification. The research results showed that the online learning process at Fatimah Pekanbaru Islamic Kindergarten had an impact on the social interactions of children aged 5-6 years, such as children not wanting to do assignments, children being less enthusiastic about participating in learning, children feeling lonely, and feel bored because you can't interact directly with friends. In this case, teachers are required to be more creative in delivering material so that children do not feel bored and children continue to be enthusiastic. Also the role of parents here is also important to maintain the stability of the child's mood in learning.